Merger and Acquisition as Drivers of Financial Performance - Padam Bahadur Lama; Prem Bahadur Budhathoki; Rita Subedi; Janga Bahadur Hamal; Mukund Kumar Chataut; Samjhana Thapa (Financial Markets, Institutions and Risks)
The purpose of the study is to examine the impact of mergers and acquisitions on financial performance in Nepalese financial institutions. This study investigated specific banks in Kathmandu, Nepal. This study, including six banks, analyzed the impact of commercial banks' pre-merger and post-merger policies on financial performance. Thus, the study consisted of 60 observations with five years of data accumulated for the analysis. Earnings per share (EPS), non-performing loan ratio (NPLR), capital adequacy ratio (CAR), credit to deposit ratio (CDR), cash reserve ratio (CRR), and bank size (BS) are major predictor variables employed in the study and return on assets (ROA) as a response variable. The research design employed in the study is descriptive and casual comparative to investigate the relationship and effect of predictors on return on assets. Therefore, the data analysis process is accomplished through descriptive statistics, correlation, and regression analysis. The findings of the study showed a positive effect of earnings per share on return on assets for pre-merger and post-merger. Next, the non-performing loan ratio found affecting negatively with return on assets. Similarly, the capital adequacy ratio and credit-to-deposit ratio positively influenced the return on assets. Further, the cash reserve ratio found an inverse influence on ROA only for post-merger and acquisition. However, bank size was found to adversely influence the return on assets for the pre-post-merger and acquisition. The findings of this study provide a benchmark for professionals, bankers, and policymakers to adopt strategic fit to enhance the financial performance of banks pursuing merger and acquisition strategies. This paper contributes to the existing literature by assessing the status of pre-merger and post-merger concerning financial performance.